HUBUNGAN PENGETAHUAN GIZI, ASUPAN ENERGI DAN VITAMIN C DENGAN TINGKAT KEBUGARAN PADA REMAJA LAKI-LAKI USIA 10-17 TAHUN DI SSB ASTAM TANGERANG SELATAN - Nur Indah Fajriyanti (2020)
Indonesian football sports achievements are decreasing on 2019. Indonesian football was ranked 159th out of 211 FIFA member countries on February 7, 2019 ranked 173th out of 210 FIFA member countries on December 19, 2019. The low performance of football in Indonesia is due to the low of fitness level by an athlete. This study aimed to determine the relationship between knowledge of nutrition, energy intake and vitamin C with the level of fitness in adolescent boys 10-17 years. This study used a cross sectional design with a sample of 50 soccer athletes aged 10-17 years. The study was conducted with a knowledge questionnaire instrument, a 3x24 hour Recall interview method and fitness level data were taken using the Cooper Test method. Data analyzed using the Chi Square test. The results showed that there was a significant relationship between nutrition knowledge with fitness level (p=0.021), energy intake with fitness level (p=0.025), there was no significant relationship between vitamin C intake with fitness level (p=0.779) . So, the conclusion is that there is a significant relationship between nutritional knowledge and energy intake with fitness level, there is no meaningful relationship between vitamin c intake with fitness level. Keywords : Fitness Level, Nutrition Knowledge, Energy Intake, Vitamin C Intake.